Infinite Matrix Products and the Representation of the Matrix Gamma Function - J.-C. Cortés; L. Jódar; Francisco J. Solís; Roberto Ku-Carrillo (Abstract and Applied Analysis)
We introduce infinite matrix products including some of their main properties and convergence results. We apply them in order to extend to the matrix scenario the definition of the scalar gamma function given by an infinite product due to Weierstrass. A limit representation of the matrix gamma function is also provided.